2005
DOI: 10.2298/sarh05s2137r
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus and dermatomyositis: Case report

Abstract: The association of systemic lupus erythematosus (SLE) with idiopathic polymyositis or dermatomyositis is reported to occur in the range of 4-16%. Myositis can occur before or after SLE, or sporadically both diseases can be present simultaneously. This case report concerns a 36-year-old female patient suffering from Raynaud's phenomenon, polyarthralgia in the small joints of the hands, and skin changes compatible with Gotron's indications. Symmetric proximal muscle weakness of the extremities, fever of up to 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…4,14,17,18 Our lupus myositis patients were all female which is concordant to the previous studies. 3,7,14,17,19 The study reported by Foot et al 6 suggested that lupus myositis was very similar to primary disease, in contrast to the milder descriptions of Fessel 16 and Tsokos et al 5 were less than rigorous: all but one of their patients with alleged myositis had a normal serum CK, and only 5/18 subjects had a confirmatory muscle biopsy. Although it remains unclear, some reports have indicated that this overlap syndrome follows a benign course and that the prognosis of myositis associated with SLE is reputed to be better than primary myositis in terms of morbidity and response to therapy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…4,14,17,18 Our lupus myositis patients were all female which is concordant to the previous studies. 3,7,14,17,19 The study reported by Foot et al 6 suggested that lupus myositis was very similar to primary disease, in contrast to the milder descriptions of Fessel 16 and Tsokos et al 5 were less than rigorous: all but one of their patients with alleged myositis had a normal serum CK, and only 5/18 subjects had a confirmatory muscle biopsy. Although it remains unclear, some reports have indicated that this overlap syndrome follows a benign course and that the prognosis of myositis associated with SLE is reputed to be better than primary myositis in terms of morbidity and response to therapy.…”
Section: Discussionsupporting
confidence: 92%
“…In the literature, SLE associated with myositis occurs in 4–16% of cases. 14 In contrast to myalgia which can affect nearly half of patients with SLE, true myositis is relatively rare as shown also by our study. 15 Myositis can occur before, after SLE (case 2), or sporadically both diseases can be present simultaneously (cases 1, 3, 4, 5 and 6 in our series).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Case reports have described PM or IIM being associated with systemic lupus erythematosus, 10 scleroderma, 11 Sjögren's syndrome 12 and myasthenia. PM-associated death is often due to lung fibrosis and severe infection.…”
Section: Discussionmentioning
confidence: 99%
“…Lupus erythematosus has been reported to occur in association with DM in the range of 4%-16%. 21 Furthermore, cases of subcutaneous panniculitis-like lymphoma arising in patients with lupus panniculitis/lupus erythematosus have been described. However, these have universally been described as T-cell processes not limited to the subcutis.…”
Section: Discussionmentioning
confidence: 99%